Self-erecting inverted pendulum employing PSO for stabilizing and tracking controller - Solihin, Mahmud Iwan; Wahyudi, Martono; Akmeliawati, Rini (2009)
The main objective of this paper is to design a state feedback controller for stabilizing and tracking control of selferecting inverted pendulum employing intelligent method using particle swarm optimization (PSO). This is motivated by the fact that one has to face trial and error approach in conventional feedback control design by pole placement method or linear quadratic regulator (LQR) method via Riccati equation. The simulation results show the effectiveness of the proposed method. The proposed state feedback controller works jointly with swingup controller in the self-erecting inverted pendulum system.